Magnetic fields during high redshift structure formation - Schleicher, Dominik R. G.; Latif, M.; Schober, Jennifer; Schmidt, W.; Bovino, S.; Federrath, C.; Niemeyer, J.; Banerjee, R.; Klessen, Ralf S. (Astronomische Nachrichten, 2013)
We explore the amplification of magnetic fields in the high-redshift Universe. For this purpose, we perform high-resolution cosmological simulations following the formation of primordial halos with ∼ ⊙ 107 M, revealing the presence of turbulent structures and complex morphologies at resolutions of at least 32 cells per Jeans length. Employing a turbulence subgrid-scale model, we quantify the amount of unresolved turbulence and show that the resulting turbulent viscosity has a significant impact on the gas morphology, suppressing the formation of low-mass clumps. We further demonstrate that such turbulence implies the efficient amplification of magnetic fields via the small-scale dynamo. We discuss the properties of the dynamo in the kinematic and non-linear regime, and explore the resulting magnetic field amplification during primordial star formation. We show that field strengths of ∼ 10-5 G can be expected at number densities of ∼ 5 cm-3. (© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Gesehen am 01.07.2021